UPAYA PENINGKATAN AKSES MASYARAKAT TERHADAP JAMBAN SEHAT DI JORONG MADANG WILAYAH KERJA PUSKESMAS KAYU JAO KABUPATEN SOLOK - Putri Nilam Sari; Atika Syahira; Mery Puspawita; Tantri Shinta Putri; Sri Rahmadani; Muhammad Agung Surya; Fani Arsyad (LPPM Universitas Andalas, 2019)
In the success of achieving health development priorities for 2015-2019 through the Healthy Indonesia program, the government mobilizes all efforts and all the potential that exists both from the central, provincial, district/city, and community governments. In its implementation, health development starts from the smallest unit of society or family. This is because of the efforts to create healthy families are the starting point for the realization of healthy communities. Therefore the Ministry of Health establishes an operational strategy for health development through the Healthy Indonesia Program with a Family Approach with 12 indicators, one of them is all families having access to or using healthy latrines. One of the districts that becomes concern of the West Sumatra Provincial Health Office is Solok Regency where only 48.57% of families have access to or use healthy latrines. This figure is below the target of the Healthy Indonesia Indicator. For this reason, through the ‘Pengalaman Belajar Lapangan’ (PBL) program, efforts were made to increase access to healthy latrines through counseling and triggering of healthy latrines, leaflet distribution, and giving sticker for homes that have used healthy latrines. It is recommended that the health center improve cooperation with various parties to be able to help the community in building more suitable latrines.